Validation of a spectrophotometric method to determine ciprofibrate content in tablets - Guilherme Nobre Lima do Nascimento; Daniel Lerner da Rosa; Hisao Nishijo; Tales Alexandre Aversi-Ferreira (Universidade de São Paulo, 2011)
Ciprofibrate is a drug indicated in cases of hypertriglyceridemia and mixed hyperlipidemia, but no monographs are available in official compendia for the analysis of this substance in tablets. The objective of this work was to develop and validate a spectrophotometric method for routine analysis of ciprofibrate in tablets. In this study, commercial and standard ciprofibrate were used, as well as placebo in absolute ethanol, analyzed by UV spectrophotometer. All tests followed the rules of Resolution RE-899, 2003. The results showed that the developed and validated method offers low cost, easy implementation, precision and accuracy, and may be included in the routine of quality control laboratories. O ciprofibrato é um fármaco indicado em casos de hipertrigliceridemia e hiperlipidemia mista, mas não há monografias em compêndios oficiais para a análise desta substância em comprimidos. O objetivo deste trabalho é desenvolver e validar um método espectrofotométrico para análise de rotina de ciprofibrato em comprimidos. Neste estudo foram empregados ciprofibrato comercial, padrão e placebo em etanol absoluto, analisadas por espectrofotometria UV. Todos os testes seguiram as regras da Resolução RE- 899, 2003. Os resultados mostraram que o método desenvolvido e validado apresenta baixo custo, fácil implementação, precisão e exatidão e pode ser incluído em rotina de laboratórios de controle de qualidade.